Profile of Elementary School Student’s Numeracy Literacy in Solving Fractions using the Minimum Competency Assessment (AKM) Model - Yuniawatika; Zulaeka Setya Luky (LPPM Universitas Buana Perjungan Karawang, 2026)
The purpose of this study was to analyze students ability to solve mathematical problems involving fractions. This study used a descriptive qualitative method. The subjects of this study were fifth-grade students at SDN Bendogerit 1 in Blitar City, East Java. Data collection techniques used purposive sampling based on scores categorized as very low, low, medium, and high. The sampling technique used was a snowball sampling. This study used Miles and Huberman's data analysis technique, which consists of three methods, including data reduction, data presentation, and conclusion drawing or verification. This study used a test instrument consisting of 5 questions in the form of AKM questions, including complex multiple choice, matching, multiple-choice, and essay questions, which was 58.46%, while matching questions were 28.18%, multiple-choice questions were 23.63%, and essay questions were 10.90%. In essay questions, most students were unable to solve the problems.